PERTUMBUHAN DAN PRODUKSI RUMPUT GAJAH (Pennisetum purpureum) PADA INTERVAL DEFOLIASI YANG BERBEDA: THE GROWTH AND PRODUCTION OF ELEPHANT GRASS (Pennisetum purpureum) ON DIFFERENT INTERVAL OF DEFOLIATION - Daniel Y. Seseray; Evi W. Saragih; Yeldrik Katiop (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2012)
The aims of this study were to determine the effect of defoliation interval of elephant grass on the growth and production and arranged in Randomized Block Design consisted of 5 blocks and 3 treatments, so there were 15 experimental units. The treatments used were P1 (defoliation 20th day), P2 (defoliation 40th day) and P3 (defoliation 60th day). The finding showed that the responses of the interval defoliation treatments were significantly different (P< 0.05) to the average height of plants and the production of dry matter (DM), where the results of further BNJ tests showed that plant height at treatment P1 (81.78 cm) was different markedly lower than P2 treatment (103.6 cm) and P3 (129.24 cm), as well as different treatment markedly lower P2 from P3 treatment. The production of DM in treatment P1 (1.20 tons/ha) did not differ significantly with treatment P2 (1.94 tons/ha), but significantly higher than the treatment P3 (2.75 tons/ha), while the P2 treatment did not differ significantly by treatment with P1 and P3. The average number of tillers and fresh forage production in treatment P1, P2 and P3 respectively 1.75 tillers and 14.15 tons/ha; 3.44 tillers and 13.07 tons/ha; 4.25 tillers and 1707 tons/ha. Concluded that the longer the interval the higher defoliation of plant growth, additional number of tillers and the higher DM production, while the production of fresh forage is relatively the similar.